Bone Plug Versus Suture-Only Fixation of Meniscal Grafts: Effect on Joint Contact Mechanics During Simulated Gait. (July 2014) - Wang, Hongsheng; Gee, Albert O.; Hutchinson, Ian D.; Stoner, Kirsten; Warren, Russell F.; Chen, Tony O.; Maher, Suzanne A.
Background: Meniscus allograft transplantation (MAT) is primarily undertaken to relieve the symptoms associated with meniscal deficiencies. However, its ability to restore normal knee joint contact mechanics under physiological loads is still unclear. Purpose: To quantify the dynamic contact mechanics associated with 2 commonly used fixation techniques in MAT of the medial compartment: transosseous suture fixation via bone plugs and suture-only fixation at the horns. Study Design: Controlled laboratory study. Methods: Physiological loads to mimic gait were applied across 7 human cadaveric knees on a simulator. A sensor placed on the medial tibial plateau recorded dynamic contact stresses under the following conditions: (1) intact meniscus, (2) MAT using transosseous suture fixation via bone plugs at the anterior and posterior horns, (3) MAT using suture-only fixation, and (4) total medial meniscectomy. A "remove-replace" procedure was performed to place the same autograft for both MAT conditions to minimize the variability in graft size, geometry, and material property and to isolate the effects of the fixation technique. Contact stress, contact area, and weighted center of contact stress (WCoCS) were quantified on the medial plateau throughout the stance phase. Results: Knee joint contact mechanics were sensitive to the meniscal condition primarily during the first half of the gait cycle. After meniscectomy, the mean peak contact stress increased from 4.2 ± 1.2 MPa to 6.2 ± 1.0 MPa ( P = .04), and the mean contact area decreased from 546 ± 132 mm 2 to 192 ± 122 mm 2 ( P = .01) compared with the intact meniscus during early stance (14% of the gait cycle). After MAT, the mean contact stress significantly decreased with bone plug fixation (5.0 ± 0.7 MPa) but not with suture-only fixation (5.9 ± 0.7 MPa). Both fixation techniques partially restored the contact area, but bone plug fixation restored it closer to the intact condition. The location of WCoCS in the central cartilage region (not covered by the meniscus) shifted peripherally throughout the stance phase. Bone plug fixation exhibited correction to this peripheral offset, but suture-only fixation did not. Conclusion: Under dynamic loading, transosseous fixation at the meniscal horns provides superior load distribution at the involved knee compartment after meniscal transplantation compared with suture-only fixation. Particular attention should be directed to the ability of medial MAT to function during the early stance phase. Clinical Relevance: Transosseous fixation via bone plugs provides superior load distribution of a transplanted meniscal allograft compared with suture fixation alone at time zero.